2010
DOI: 10.1016/j.bbapap.2009.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of advanced glycation endproduct synthesis by kynurenines in human lens proteins

Abstract: Human lens proteins (HLP) become chemically modified by kynurenines and advanced glycation end products (AGEs) during aging and cataractogenesis. We investigated the effects of kynurenines on AGE synthesis in HLP. We found that incubation with 5 mM ribose or 5 mM ascorbate produced significant quantities of pentosidine, and this was further enhanced in the presence of two different kynurenines (200-500 µM): N-formylkynurenine (Nfk) and kynurenine (Kyn). Another related compound, 3-hydroxykynurenine (3OH-Kyn), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The risk factors attributed to the onset of cataracts include aging, diabetes, exposure to UV light, hypertension, and oxidative stress [ 55 ]. ROS cause cross-linking and degradation of lens proteins, thereby initiating cataractogenesis [ 56 ]. Padmanabha and Vallikannan [ 57 ] showed that eicosapentaenoic acid and docosahexaenoic acid increased the anti-cataract activity of lutein.…”
Section: Lutein In Inflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk factors attributed to the onset of cataracts include aging, diabetes, exposure to UV light, hypertension, and oxidative stress [ 55 ]. ROS cause cross-linking and degradation of lens proteins, thereby initiating cataractogenesis [ 56 ]. Padmanabha and Vallikannan [ 57 ] showed that eicosapentaenoic acid and docosahexaenoic acid increased the anti-cataract activity of lutein.…”
Section: Lutein In Inflammatory Diseasesmentioning
confidence: 99%
“…Thus, it prevents age-related macular degeneration. In addition, lutein prevents oxidative stress-mediated G2/M arrest and apoptosis in retinal pigmental epithelial cells [ 48 ] and cross-linking and degradation of lens proteins which prevents cataractogenesis [ 56 ]. IL, interleukin; MCP-1; monocyte chemoattratant protein-1; ROS, reactive oxygen species; STAT, signal transducer and activator of transcription; TNF-α, tumor necrosis factor-α.…”
Section: Figurementioning
confidence: 99%
“…Thus, a vicious cycle could form in which AGEs promote AGE synthesis and consequently propagate lens protein modification. We have previously shown that 3OHKyn can promote pentosidine synthesis from ASC under aerobic conditions (74). Thus, there may be additional UVA-independent mechanisms for the formation of AGEs in lens proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The kynurenine pathway and ascorbate-mediated AGE synthesis in the lens appear to be interlinked because kynurenines modulate AGEs synthesized from ascorbate (26). In addition, kynurenines become photosensitizers upon UVA light exposure and stimulate ascorbate oxidation, thereby promoting AGE synthesis in lens proteins (27).…”
mentioning
confidence: 99%